1993
DOI: 10.1046/j.1365-2648.1993.18101651.x
|View full text |Cite
|
Sign up to set email alerts
|

The discipline of nursing: historical roots, current perspectives, future directions

Abstract: As advances in nursing science and research impact upon nursing education and clinical practice, new ways of looking at phenomena have led to a re-examination and refinement of the traditional concepts: person, environment, health and nursing. This evolving pattern of intellectual growth holds promise for the discipline of nursing through the advancement of knowledge based upon scientific inquiry into the practice of nursing. This paper discusses nursing as a discipline by examining the development of a unique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…Previous studies have indicated a low level of nursing research competence among clinical nurses (Corchön, ; Jing et al, ; Wang & Yang, ) and have reported positive correlations between nursing research competence and individual characteristics (i.e. age, educational level, nursing work experience, nursing research experience and research education experience) (Czerwinski et al, ; Dipn, ; Jing et al, ; Shaw, ; Smirnoff, Ramirez, Kooplimae, Gibney, & McEvoy, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have indicated a low level of nursing research competence among clinical nurses (Corchön, ; Jing et al, ; Wang & Yang, ) and have reported positive correlations between nursing research competence and individual characteristics (i.e. age, educational level, nursing work experience, nursing research experience and research education experience) (Czerwinski et al, ; Dipn, ; Jing et al, ; Shaw, ; Smirnoff, Ramirez, Kooplimae, Gibney, & McEvoy, ).…”
Section: Introductionmentioning
confidence: 99%
“…Nursing is developing into an independent discipline and evidence‐based practice profession. Therefore, high‐quality nursing research calls for the construction of a knowledge base for the nursing discipline and evidence‐based practice (Polit & Beck, ; Shaw, ). Clinical nurses, who are the end‐users and producers of nursing research, play an important role in the consumer–producer continuum in nursing research.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that she later denounced the prevailing notion that any woman could According to Shaw (1993) Nightingale was the first to delineate that which she considered nursing's goal and be a 'good' nurse, this concept predominated for over a century (McCloskey & Grace 1990). Following Nightingale the business of nurses was therefore seen as women's work, subordinate to medicine, caring for the sick, preventing all conditions detrimental to the health of the individual.…”
Section: Foundation Of Modern Nursingmentioning
confidence: 99%
“…(Leininger 1984 pp. 4-5) Concerned at this apparent perpetual disagreement as to 'Care', according to Alexander et al (1989) in a personal the focus of nursing's work, which they contend has communication with Leininger, referred to: inhibited the development of nursing theory and consequently nursing as a profession, Yura & Torres (1975), phenomena related to assistive, supportive or enabling behaviour Donaldson & Crowley (1978), Fawcett (1978, Flaskerud & towards or for another individual (or group) with evident or antici-Halloran (1980) Meleis (1987) and later Shaw (1993), in pated needs to ameliorate or improve a human condition or examining the work of the major nurse theorists and, in lifeway.…”
Section: Nursing As Caringmentioning
confidence: 99%
See 1 more Smart Citation